Fruit Enzyme Activity of Molasses Combination Against Control of S. Aureus and E. Coli Bacteria - Adrianto, Ari; Khalish, Faishal; Pratiwi, Dwita Cahaya (Journal of Sustainable Materials Processing and Management, 2022)
This study aims to determine the effect of the pineapple and orange peel enzymes combined with molasses on the effectiveness of the inhibition zones of gram positive (S. Aureus) and gram negative (E. Coli) bacteria. The study was conducted using the disc method, where the bacterial samples used were at a concentration of 200 millimicrons. And the addition of enzyme solution with a concentration of 20 millimicrons. In observations using Scan 500, the results obtained in samples of pineapple peel with the highest inhibition zones for E. Coli and S. Aureus bacteria, respectively, of 11.7 mm and 12.8 mm. Meanwhile, in the test of orange peel samples, the highest inhibition zones for E. Coli and S. Aureus were 16.6 mm and 13.2 mm, respectively. In addition, the highest pH testing of each sample of orange peel and pineapple was obtained on the third fermentation with values of 4.63 and 4.39.